Hubungan Antara Hasil UAN SMP dengan Prestasi Belajar Peserta Didik SMA - Iin Nurbudiyani; Muhammad Fatchurahman; Endang Sri Suyati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The technique analysis data used is: a) Percentege analysis technique, to achieving or obtaining the clarity about The National Final Exam results of Junior High School and learning achievement of students at 1st and 2nd semester; and b) Correlation techniques of product moment used to see how far the variables that are related to each other. The result of this research was: (1) the first grade students at 1st semester of Senior High School which have good exam results is relatively small, while the students which have less The National Final Exam result is relatively small also. Therefore it can be said that Senior High School students from The National Final Exam results of Junior High School is relatively quite enough; (2) The first grade students at 1st semester of Senior High School which have good achievement is relatively small, while the students which have less achievement is relatively small also. Therefore it can be said that learning achievement of Senior High School students at 1st semester is relatively quite enough; (3) the first grade students at 2nd semester of Senior High School which have good achievement is relatively small, while the students which have less achievement is relatively small also. Therefore it can be said that learning achievement of Senior High School students at 2nd semester is relatively quite enough; (4) There is significant relationship between The National Final Exam results of Junior High School and students at the 1st and 2nd semester learning achievement of Senior High School.